2002
DOI: 10.1161/01.cir.0000041250.89627.a9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Benefit From Intravenous Platelet Glycoprotein IIb/IIIa Receptor Inhibition as Adjunctive Treatment for Percutaneous Interventions of Aortocoronary Bypass Grafts

Abstract: Background-Despite widespread use of platelet glycoprotein (GP) IIb/IIIa receptor inhibitors for percutaneous coronary interventions (PCI) of bypass grafts, data supporting this strategy are lacking. Methods and Results-A pooled analysis of 5 randomized intravenous GP IIb/IIIa inhibitor trials (EPIC, EPILOG, EPISTENT, IMPACT II, and PURSUIT) was performed, and outcomes of graft interventions were assessed at 30 days and 6 months. Compared with PCI of native circulation (nϭ13 158), graft interventions (nϭ627) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(97 citation statements)
references
References 30 publications
2
94
0
1
Order By: Relevance
“…PCI of de novo SVG stenosis is considered a high-risk intervention because SVG atheroma is friable and more prone to distal embolization. A pooled analysis of five RCTs shows that GPIIb IIIa inhibitors are less effective for SVG PCI than for PCI of native vessels [212]. Many different approaches have been evaluated to prevent distal embolization of particulate debris, including distal blocking/aspirating, proximal blocking, suction, filtering, or mesh-based devices [171].…”
Section: Saphenous Vein Graft Diseasementioning
confidence: 99%
“…PCI of de novo SVG stenosis is considered a high-risk intervention because SVG atheroma is friable and more prone to distal embolization. A pooled analysis of five RCTs shows that GPIIb IIIa inhibitors are less effective for SVG PCI than for PCI of native vessels [212]. Many different approaches have been evaluated to prevent distal embolization of particulate debris, including distal blocking/aspirating, proximal blocking, suction, filtering, or mesh-based devices [171].…”
Section: Saphenous Vein Graft Diseasementioning
confidence: 99%
“…Although initial experience with GPIIb/IIIa antagonists in PCI of vein grafts was encouraging, a meta-analysis revealed that adjunctive GPIIb/ IIIa antagonist therapy including abciximab or eptifibatide have failed to improve the outcome of percutaneous bypass graft interventions. Besides, it was also associated with higher incidence of major bleedings (6.8% vs 1.4% in placebo) and minor bleedings (14.9% vs 8.1% in placebo) (Roffi et al 2002). In our study, the PCI was performed after two days of tirofiban administration; however in the aforementioned meta-analysis, abciximab or eptifibatide were used during the PCI procedure.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, the routine use of glycoprotein IIb/IIIa receptor blockers during PCI of SVG has not been shown to be beneficial at reducing major adverse cardiac events. 21,22 Intracoronary calcium channel blockers, adenosine, and nitroprusside are commonly used to treat the no-reflow phenomenon caused by distal embolization but have not been shown to prevent embolization per se.…”
Section: Indications For Epds Svg Interventionmentioning
confidence: 99%